Toricelli-Based Defensive Riding Training for Peer Educators of SMKN 1 Banjarbaru Students - Vina Yulia Anhar; Istiana Istiana; Ihya Hazairin Noor; Zuhrufa Wanna Yolanda; Hafiz Akmal Hidayatullah Al-Ayyudi; M Naufal Hibatullah (Lambung Mangkurat, 2024)
Defensive riding training is a strategy that helps motorcyclists to always be in control and not be surprised by the actions of others. SMK Negeri 1 Banjarbaru, a school with many students using motorbikes for transportation, is located in an area with high-traffic accidents. This activity aims to provide students with an understanding of how to drive defensively and Toricelli-based. The method of implementing the service is to form peer educators, as many as six people from students aged 17 or this year aged 17, given education and training on Toricelli-based defensive riding training. The organizer evaluates knowledge through a pre-post test. The evaluation results showed increased knowledge about defensive riding training in students of SMKN 1 Banjarbaru.The role of peer educators of SMKN 1 Banjarbaru students can continue to remind their peers of the importance of safe driving culture, so that the role of peer educators does not only stop when this activity ends.